STRUKTUR KEPEMILIKAN MANAJERIAL, RISIKO BISNIS, DAN KEBIJAKAN KEUANGAN: ANALISIS PERSAMAAN - Arif Afendi (SEGMEN Jurnal Manajemen dan Bisnis, 2014)
This study examines interdependence relationship between managerial ownership structure, risk, debt policy and dividend policy in explaining agency theory. Agency theory argues that managerial ownership structure, debt policy and dividend policy can be used as a mechanism in taking control of any agency conflict. The sample used in the study was a manufacturer publishing and listing its shares at Indonesian Stock Exchange in 2004-2009. This study used Three Stage Least Square method to examine the interdependence relationship between managerial ownership, risk, debt policy and dividend policy. The findings showed that there was an interdependence relationship between managerial ownership, risk, debt policy and dividend policy, but no interdependence relationship between risk with debt policy and dividend policy. Furthermore, it also revealed that there was complementary relationship between managerial ownership with debt policy and dividend policy. On the other hand, there was substitutional relationship between debt policy and dividend  policy in terms of controlling agency conflict. Key words: agency theory, managerial ownership, risk, debt policy, dividend policy